SPORT DEVELOPMENT INDEX (SDI) IN LANGKAT DISTRICT - Nugroho, Agung (Gladi : Jurnal Ilmu Keolahragaan, 2024)
The objective of this study is to assess the degree of community engagement, physical fitness, and sports advancement in the Langkat District, using the community involvement index and physical fitness index for the year 2020. This study employed a descriptive evaluation strategy, survey research, and quantitative methods. The research sample comprised a total of ninety individuals from Langkat District. Questionnaires and evaluation processes were utilised as data gathering approaches. The precision of the measuring device is one of the factors that make up the Sport Development Index (SDI). The subsequent passage provides a concise overview of the discoveries made in this investigation. (1) The community participation index was computed to be 0.388. (2) The community's physical fitness score of 0.351 suggests that the degree of sports engagement in the community is at a low level. This is evident from the community engagement index, which indicates that the degree of community fitness is insufficient. The community's fitness level is low, as seen by the community physical fitness index. Moreover, the indicator of 0.369 signifies a low level of sports growth in relation to community involvement and physical well-being. Ultimately, the indicators for community involvement, physical well-being, and athletic advancement in Langkat District are all significantly deficient.